2021
DOI: 10.3390/ijms22062853
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Oral Selegiline Treatment Mitigates Age-Related Hearing Loss in BALB/c Mice

Abstract: Age-related hearing loss (ARHL), a sensorineural hearing loss of multifactorial origin, increases its prevalence in aging societies. Besides hearing aids and cochlear implants, there is no FDA approved efficient pharmacotherapy to either cure or prevent ARHL. We hypothesized that selegiline, an antiparkinsonian drug, could be a promising candidate for the treatment due to its complex neuroprotective, antioxidant, antiapoptotic, and dopaminergic neurotransmission enhancing effects. We monitored by repeated Audi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 78 publications
1
4
0
Order By: Relevance
“…The BALB/c mice strain is characterized by early hearing loss and therefore also serves as a model for age-related hearing loss. In a study by Szepesy et al [41] a similar progression of hearing thresholds was noted in all frequencies. Willott et al [42], demonstrated in BALB/c mice model that aging was associated with progressive loss of hair cells and spiral ganglion cells (SGCs), most prominently between 4 and 10 months of age.…”
Section: Discussionsupporting
confidence: 53%
“…The BALB/c mice strain is characterized by early hearing loss and therefore also serves as a model for age-related hearing loss. In a study by Szepesy et al [41] a similar progression of hearing thresholds was noted in all frequencies. Willott et al [42], demonstrated in BALB/c mice model that aging was associated with progressive loss of hair cells and spiral ganglion cells (SGCs), most prominently between 4 and 10 months of age.…”
Section: Discussionsupporting
confidence: 53%
“…The inbred BALB / c mouse strain shows age-related hearing loss and is also used as a presbycusis model [ 34 , 35 ]. Detailed anatomy of the organ of Corti and their cells vary in different mice strains, most prominently in the apical region [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have performed our experiments on DCs in the apical and middle turns in the hemicochlea preparation. These turns include the most relevant frequency region of the basal membrane (~0.5–30 kHz; [ 35 , 51 ]), and the success rate of perfect basal region cut during the hemicochlea preparation is low.…”
Section: Methodsmentioning
confidence: 99%
“… Cassinotti et al (2022) overexpressed neurotrophin-3 (Ntf3) in mouse cochlea starting at middle age, thereby preventing age-related inner hair cell synaptopathy and slowing age-related hearing loss. Oral treatment with selegiline, a neuroprotective antiparkinsonian drug, significantly alleviated hearing loss at higher frequencies in mice with moderate hearing loss, but not in mice with rapid progressive hearing loss ( Szepesy et al, 2021 ). We believe that the drug treatment of presbycusis has broad prospects, but the current application is still concentrated in animal models and clinical trials, and its clinical application still needs to solve problems such as efficacy, safety, administration route and dosage.…”
Section: Introductionmentioning
confidence: 99%